A Qualitative Study on Working Experience of Rural Doctors in Malappuram District of Kerala, India - Vinod Vallikunnu, Ganesh Kumar S.,Sonali Sarkar, Sitanshu Sekhar Kar, Harichandrakumar K. T (Journal of Family Medicine and Primary Care, 2014)
Background: Improving the working conditions of rural doctors is an important issue to increase the quality of health services to target groups. Objectives: To assess the working experience of rural doctors at primary health care level. Materials and Methods: This qualitative study was conducted among 30 medical officers from 21 primary health centers in Malappuram district of Kerala, India. In-depth interview was conducted, and content analysis was performed with the identification of themes based on the responses obtained. Results: There were 19 males and 11 females belonged to 25 to 55 years age group. About 70% (21) of them were graduates with MBBS qualification, and the rest were postgraduates. About 2/3 rd of them (20) had experience of less than 5 years. They expressed difficulty in managing the work in stipulated time period. However, this had never affected their OP management in anyway. They told that higher authorities were supportive, but they faced some opposition from the public in implementation of national program. Few opined that the training received was grossly insufficient in running the administrative affairs of the health center. Most of them satisfied with physical infrastructure, but manpower including medical officers and supporting staff were not sufficient. Some opined that the age of retirement is too early and should be increased. They participated in Continuing Medical Education, but expressed that it’s content should suit to primary health care level. Conclusion: This study highlighted their concern to patient care and time, field work, administrative work, infrastructure, professional development, and future prospects. Further large scale evaluation studies will explore the situational analysis of it.